INTERVIEW WITH PROF. NICO NORMAN KOOPMAN - M. Laubscher (Acta Theologica)
Nico Koopman is Deputy Vice-Chancellor: Social Impact, Transformation and Personnel at Stellenbosch University, and Professor of Systematic Theology, Ethics and Public Theology. He is also an ordained pastor of the Uniting Reformed Church in Ida’s Valley, Stellenbosch. He served as pastor in the congregations of Atlantis, Westfleur-Atlantis, and Bellville (as university chaplain and youth minister). He was Vice-Rector of Huguenot College in Wellington, and later Dean of the Faculty of Theology at Stellenbosch University. He was a founding member and chairperson of the Global Network for Public Theology and is a fellow of the Institute for Theological Inquiry in Princeton, New Jersey. His research focuses on themes such as inalienable dignity, healing reconciliation, embracive justice, responsible freedom, equality, as well as the reciprocal and transformative impact of universities on various spheres of society, including politics, economics, the natural environment, civil society, and public opinion-formation. He is involved in public discourses in the academy, churches and broader society, both locally and internationally.